Chapter «Мы смеялись, словно от щекотки по сердцу». Мутная исповедь у Достоевского - GHIDINI, Maria Candida (Biblioteca di Studi Slavistici, 2023)
"We laughed like from a tickle on the heart." Dostoevsky's Muddy Confession. When considering laughter in Dostoevsky, one immediately thinks of the long "tirade" in The Adolescent, which proposes a kind of physiology of laughter, and its unpredictable effects on the perception of those who witness it. Laughter and caustic humor color even the most intimate confessions and can serve to partially mask the difficult action of revealing oneself before others. Modernity itself is the era of self-exhibition, of a sort of widespread confession. And yet, the laughter of modernity has lost the essence of joy. Joy is a function of that almost impossible sincerity that unveils the essence of man. The grimace of the fool, who shamelessly denudes himself before others in confession, becomes a sign of the isolation of the modern self and the end of the utopia of sincerity pursued by Rousseau.